2009
DOI: 10.3311/pp.ch.2009-2.08
|View full text |Cite
|
Sign up to set email alerts
|

pH-dependent surface charging of metal oxides

Abstract: Aqueous dispersions of metal oxide particles are of great practical interest due to their wide-ranging industrial applications and everyday uses under the conditions required. The latter involves the broad variability of pH and dissolved materials among them electrolytes which have definite role in charge neutralization in the vicinity of particle surface. In this work, the pH-dependent surface charging of metal oxides due to the specific adsorption of H + /OH − in the presence of indifferent and specific ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 28 publications
(34 reference statements)
1
35
0
1
Order By: Relevance
“…Adsorption of organic anions via anion exchange (or electrostatic interaction) is greatest within the range of pH values below the PZC and above the pKa wherein the charge on mineral surfaces and acidic organic groups are opposite (Murphy et al 1990(Murphy et al , 1992Tipping 1981;Davis 1982). A theoretical optimal range for reaction of carboxylic acid moieties with surface hydroxyl groups on Fe and Al oxide mineral phases of opposite charge as a function of pH can be calculated from the Nernst equation (Tomba´cz 2009) to estimate surface charge potential for metal oxides and the percent of dissoci-ated carboxylic acid groups can be obtained from the Hendersson-Hasselbach equation (Supplemental Material). Assuming a PZC value for hydrous ferric oxide of 8.1 and 6-7 for goethite (Smith 1999) and a pKa of 4.4 for IHSS humic acid representing a model of soil organic matter (Ritchie and Perdue 2003), we found an optimal range for electrostatically mediated adsorption of humic acid at 4-8.1 and 4-7.5 for ferrihydrite and goethite respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Adsorption of organic anions via anion exchange (or electrostatic interaction) is greatest within the range of pH values below the PZC and above the pKa wherein the charge on mineral surfaces and acidic organic groups are opposite (Murphy et al 1990(Murphy et al , 1992Tipping 1981;Davis 1982). A theoretical optimal range for reaction of carboxylic acid moieties with surface hydroxyl groups on Fe and Al oxide mineral phases of opposite charge as a function of pH can be calculated from the Nernst equation (Tomba´cz 2009) to estimate surface charge potential for metal oxides and the percent of dissoci-ated carboxylic acid groups can be obtained from the Hendersson-Hasselbach equation (Supplemental Material). Assuming a PZC value for hydrous ferric oxide of 8.1 and 6-7 for goethite (Smith 1999) and a pKa of 4.4 for IHSS humic acid representing a model of soil organic matter (Ritchie and Perdue 2003), we found an optimal range for electrostatically mediated adsorption of humic acid at 4-8.1 and 4-7.5 for ferrihydrite and goethite respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that the sediment was rich in major metal oxides such as CaO, MgO, Fe 2 O 3 , and Al 2 O 3 , as well as minerals such as quartz and clays. The metal oxide surfaces are positively charged and the mineral surfaces are negatively charged at the experimental pH ($7.3) due to surface chemical reactions with H + /OH À ions, respectively (Tombácz, 2009). Consequently, the aquifer sediment surface is expected to be chemically heterogeneous and possess a distribution of negative and positive surface charges.…”
Section: Characterization Of Aquifer Sedimentmentioning
confidence: 99%
“…80 These chemical reactions are evidenced to be the primary surface charging mechanism for hydrated silica, 58 with electrolyte effects having a measurable but less significant effect. 81 Ionic strength can be important, for example, for ultrapure water (<0.001 M); negligible surface ionisation can occur due to the lack of availability of charge stabilising cations. 82 In the present work, the ionic strength of the simulated system was 300 mM.…”
Section: Silica Surface Chemistrymentioning
confidence: 99%